Botucatu, Brazil: A Regional Community Palliative Care Model - Lemonica, Lino [UNESP]; Barros, Guilherme A.M. [UNESP] (Elsevier, 2007)
The Pain Management and Palliative Care Service in the Department of Anesthesia at Botucatu Medical School, UNESP is a pioneer in Brazil. Based on an interdisciplinary team that provides specialized inpatient, ambulatory outpatient, and home care to patients in Botucatu and the surrounding region, the service is also able to provide extensive educational opportunities in pain management and palliative care for medical students, anesthesia residents, practicing anesthetists, and nurses. © 2007 U.S. Cancer Pain Relief Committee.
Keywords: Anesthesia; Brazil; education; home care; palliative care; amitriptyline; bisphosphonic acid derivative; carbamazepine; codeine; fentanyl; gabapentin; methadone; morphine; nonsteroid antiinflammatory agent; opiate; paracetamol; chronic pain; continuing education; health care access; health service; human; medical specialist; medical student; outpatient care; palliative therapy; Community Health Services; Education, Medical; Education, Nursing; Humans; Pain; Palliative Care; Regional Medical Programs